PHOTOGRAPHY AS A DOCUMENT OF TIME: VISUAL NARRATIVES IN URBANISM AND SOCIAL MEMORY - Elizabeth Glazko (Modern American Journals, 2025)
This article analyzes photography as a tool for documenting time and shaping visual narratives in urban studies and social memory. It examines the dual nature of photography: as a means of capturing reality and as a mechanism for interpreting it. Particular attention is paid to the role of photographic images in constructing collective identity, preserving urban memory, and visualizing social transformations. The work draws on contemporary research in visual culture, urban studies, and the sociology of memory.
Keywords: Photography, document of time, visual narratives, urban studies, social memory, visual culture, urban environment, archive, identity, cultural heritage.